1) \(f\left(x\right)=-3x^2-12x+5\)
\(\Rightarrow f\left(x\right)=-3\left(x^2+4x\right)+5\)
\(\Rightarrow f\left(x\right)=-3\left(x^2+4x+4\right)+5+12\)
\(\Rightarrow f\left(x\right)=-3\left(x+2\right)^2+17\le17\left(-3\left(x+2\right)^2\le0,\forall x\right)\)
\(\Rightarrow GTLN\left(f\left(x\right)\right)=17\left(tạix=-2\right)\)
2) \(f\left(x\right)=-8x^2+20x\)\
\(\Rightarrow f\left(x\right)=-8\left(x^2+\dfrac{5}{2}x\right)\)
\(\Rightarrow f\left(x\right)=-8\left(x^2+\dfrac{5}{2}x+\dfrac{25}{16}\right)+\dfrac{25}{2}\)
\(\Rightarrow f\left(x\right)=-8\left(x+\dfrac{5}{4}\right)^2+\dfrac{25}{2}\le\dfrac{25}{2}\left(-8\left(x+\dfrac{5}{4}\right)^2\le0,\forall x\right)\)
\(\Rightarrow GTLN\left(f\left(x\right)\right)=\dfrac{25}{2}\left(tạix=-\dfrac{5}{4}\right)\)